Liver-expressed Cd302 and Cr1l limit hepatitis C virus cross-species transmission to mice - Brown, Richard J.P.; Dao Thi, Viet Loan (Science advances, 2020)
Hepatitis C virus (HCV) has no animal reservoir, infecting only humans. To investigate species barrier determinants limiting infection of rodents, murine liver complementary DNA library screening was performed, identifying transmembrane proteins Cd302 and Cr1l as potent restrictors of HCV propagation. Combined ectopic expression in human hepatoma cells impeded HCV uptake and cooperatively mediated transcriptional dysregulation of a noncanonical program of immunity genes. Murine hepatocyte expression of both factors was constitutive and not interferon inducible, while differences in liver expression and the ability to restrict HCV were observed between the murine orthologs and their human counterparts. Genetic ablation of endogenous Cd302 expression in human HCV entry factor transgenic mice increased hepatocyte permissiveness for an adapted HCV strain and dysregulated expression of metabolic process and host defense genes. These findings highlight human-mouse differences in liver-intrinsic antiviral immunity and facilitate the development of next-generation murine models for preclinical testing of HCV vaccine candidates. - Two transmembrane proteins cooperate to block infection of murine hepatocytes by human-tropic hepatitis C virus. - Two transmembrane proteins cooperate to block infection of murine hepatocytes by human-tropic hepatitis C virus.